2017
DOI: 10.1177/2150135117712248
|View full text |Cite
|
Sign up to set email alerts
|

Modified Aortic Uncrossing Procedure: A Novel Approach for Norwood Palliation of Complex Univentricular Congenital Heart Disease With a Circumflex Aorta

Abstract: The circumflex aorta is a rare type of true vascular ring anomaly. It consists of a retroesophageal right aortic arch, a left-sided descending thoracic aorta, and a left-sided ligamentum arteriosum. The "aortic uncrossing procedure" described by Planché and Lacour-Gayet is the procedure of choice for managing this aortic anomaly in patients with a biventricular heart. The presence of a circumflex aorta in a patient with heterotaxy syndrome and univentricular congenital heart disease requiring Norwood palliatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The surgery could also be done via a median sternotomy without cardiopulmonary bypass using the side‐biting clamp on the ascending aorta . Some modifications have been made to the uncrossing procedure to address the unusual anatomy in heterotaxy single‐ventricle hearts by incorporating the arch into the Damus‐Kaye‐Stansel anastomosis . Dealing with the circumflex aorta in the adult population is challenging as mobilization of the aorta to perform an arch advancement is extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery could also be done via a median sternotomy without cardiopulmonary bypass using the side‐biting clamp on the ascending aorta . Some modifications have been made to the uncrossing procedure to address the unusual anatomy in heterotaxy single‐ventricle hearts by incorporating the arch into the Damus‐Kaye‐Stansel anastomosis . Dealing with the circumflex aorta in the adult population is challenging as mobilization of the aorta to perform an arch advancement is extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Our technique expands on previous methods of palliating severe atrioventricular valve regurgitation. 4,5 This small case series provides evidence that a Norwood operation coupled with LVE by a fenestrated mitral valve patch, and aortic valve oversewing, leaving a small washing jet at the commissure to prevent widening/tearing of the defect, has thus far proven to be an effective method in this unique patient population. Patient 1's success demonstrated that LVE via a fenestrated PTFE patch could be safely accomplished when severe mitral valve regurgitation in a single ventricle patient is present.…”
Section: Commentmentioning
confidence: 94%
“…Patient 1 was originally described in 2017 as a complex case report; however, utilization of and expansion upon that original surgical technique in similar cases thereafter led to the more developed and reproducible palliative procedure described herein. 4…”
Section: Methodsmentioning
confidence: 99%
“…Other reported cardiac lesions include atrial septal defect and bicuspid aortic valve [14,33] . Less commonly, Tetralogy of Fallot or double outlet RV, a lesion with a higher frequency of right aortic arch than in the normal population, had also been reported in circumflex aorta [15] ; as well as left heart hypoplasia [5,34] .…”
Section: Concomitant Lesionsmentioning
confidence: 99%
“…Cardiopulmonary bypass with deep hypothermic total circulatory arrest can be used; but we preferred the strategy of selective antegrade cerebral perfusion via the innominate artery perfused via a 3 mm to 3.5 mm Goretex shunt [6] . Aortic uncrossing procedure has also been used in single ventricular physiology with aortic arch obstruction requiring a concomitant Norwood procedure [34] .…”
Section: Aortic Arch Hypoplasia or Obstructionmentioning
confidence: 99%